Safety and Security in Ultrasonography-Short Review - Farizah, Nur Hazzanita; Siti Amira Othman (Research and Innovation in Technical and Vocational Education and Training, 2022)
Diagnostic sonography is a type of ultrasound that is used to examine a person's interior bodily components. A sonogram is a method of visualizing the body's soft tissues. Organs, tissues, and blood flow are all shown. Ultrasonography is a diagnostic imaging technology that creates pictures of bodily structures using high-frequency sound waves and a transducer. Ultrasonography is the instrument used to perform sonography, which is a technique for diagnosing different disorders. A sonographer uses an ultrasound instrument to do sonography. Ultrasound employs a tiny transducer probe to send sound waves into the body as well as capture the waves that return. Sound waves go through the region being investigated until they reach a tissue barrier, such as the border between fluid and soft tissue or soft tissue and bone. The benefits of sonography include the ability for the physician to perform emergency care at the bedside quickly, the ability to visualize other structures such as the aorta, pancreas, liver, and the identification of complications such as perforation, empyema, abscess, and the absence of radiation. This review discussed several ultrasound tests that are used in medicine to change the picture of the fetus in the womb. The evaluation of whether ultrasound exposure to the baby is safe, as well as recommendations for the safe use of diagnostic ultrasound equipment, will also be conducted. The effects of the ultrasonic contrast medium were connected to particle characteristics and the interaction of microbubble destruction and ultrasound beam energy.